Use and Importance of Qualitative Research in School Education - Aryal, Saroj (The Educator Journal, 2024)
Quantitative research has long been the dominant approach in education, yet its focus on numerical data has left gaps in understanding human attributes and behaviors. Consequently, qualitative research has gained prominence in studying human-related factors across various sectors, including education. This shift prompts critical questions regarding the importance and utility of qualitative research in school education. This study explores the significance of qualitative research in the educational context, addressing key questions such as the importance of qualitative research in school education and the rationale behind its utilization. By examining and interpreting various written or recorded materials, including reports, letters, and social media posts, this study draws insights into specific phenomena within school environments. The critical paradigm serves as a crucial framework for understanding and addressing social inequalities and power imbalances within the educational system. By adopting a critical perspective, this study focuses on school-related variables through secondary documents such as articles and books, highlighting the importance of qualitative research in addressing systemic issues. Qualitative research delves into the complexities of human behavior by exploring individuals’ experiences, ideas, feelings, and behaviors. Through informal data collection techniques such as focus groups, observations, and interviews, researchers gain a comprehensive understanding of various topics. In the realm of education, qualitative research offers valuable insights that complement quantitative approaches, contributing to a holistic understanding of educational phenomena. Qualitative research plays a crucial role in enhancing our understanding of human attributes and behaviors within the educational context. By embracing diverse perspectives and methodologies, qualitative research contributes to more nuanced and comprehensive educational practices and policies.